The effect of a natural forest fire on beetle assemblages in the boreal forest of Sweden - Andersson, Jon (2008)
The aim of this study was to determine the effect of a large natural forest fire on the beetle community. Large, naturally-occurring forest fires rarely occur in north Sweden and the ecological effect on these events has therefore seldom been studied. It is, however, important to gain knowledge of natural forest fires to be able to mimic these events in conservation measures and fire management. I studied the changes in abundance, species richness and assemblage composition of beetles following the fire in 2007. I performed detailed analyses on four different groups of beetles: saproxylic beetles, beetles favoured or strongly favoured by fire, and cambium consuming beetles. In the latter group, many of the typical pest species are found. 18 traps where placed in the fire field and the same number of traps where placed in a control area close to the fire field. Data from this survey where later analysed with Wilcoxons rank sum test and PERMANOVA. The total number of species found was 335 consisting of 8586 individuals. In the fire field I caught 239 species consisting of 5507 individuals while I in the control area caught 221 species consisting of 3079 individuals. I found a significant increase in the abundance and changes in the species composition of beetles following fire. In contrast, I did not find clear evidence that the species richness was higher in the burned areas. However, my study, in agreement with earlier studies, showed that the forest fires have a strong effect on the species composition of beetles. Further research on the effects of large scale forest fire in landscapes with a long history of fire suppression is important for the development of sustainable management plans for species favoured by and adapted to fire.